2013
DOI: 10.1007/s11357-013-9579-y
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial oxidative stress is modulated by dietary fat in adipose tissue from elderly people

Abstract: We have investigated whether dietary fat modifies the postprandial oxidative stress in adipose tissue of elderly people. Twenty participants received three diets for 4 weeks each: SFA-rich diet, Mediterranean (Med) diet enriched in MUFA with virgin olive oil, and a low-fat, high-carbohydrate diet enriched in n-3 PUFA (α-linolenic acid from plant origin) (CHO-PUFA diet). After 12 h of fasting, volunteers received a breakfast reflecting the fatty acid composition of the diet ingested in the preceding dietary per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Specifics regarding participants, recruitment, and study design have been previously described in detail . Briefly, inclusion and exclusion criteria were fulfilled by a total of 20 patients (age ≥ 65 years; ten men and ten women).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Specifics regarding participants, recruitment, and study design have been previously described in detail . Briefly, inclusion and exclusion criteria were fulfilled by a total of 20 patients (age ≥ 65 years; ten men and ten women).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…After a breakfast with a similar composition to the final dietary period, samples of adipose tissue and blood (PBMCs) where taken in order to assess the nutrigenomic changes related to oxidative stress and inflammatory response, depending on the dietary fat administered. Meza-Miranda et al, 2014 andCamargo et al, 2012, showed an increase in the postprandial gene expression profile of the antioxidant defense system due to the consumption of TMD and CHO-PUFA diet compared with the SFA-rich diet. Camargo et al, 2012 observed that TMD (MUFA) consumption reduces the expression of several inflammatory genes compared to SFArich (p65 and MCP-1) and CHO-PUFA diets (p65 and TNF-a), increases the expression of the antiinflammatory gene IkBa and decreases the MMP-9 plaque instability marker gene expression.…”
Section: Postprandial Inflammatory Response To the Polyphenols Of Olimentioning
confidence: 99%
“…Both genes are involved in inflammation processes and their transcriptomic changes might underlie cardio-protective effects due to the intake of VOO and nuts. Meza-Miranda et al, 2014, andCamargo et al, 2012, conducted a crossover postprandial trial in 20 healthy elderly people who followed three diets for 3-week periods each. The diets differed in the fat type; SFA-rich, TMD+VOO (MUFA) and CHO-PUFA.…”
Section: Postprandial Inflammatory Response To the Polyphenols Of Olimentioning
confidence: 99%
“…Oxidative stress associated with obesity originates from many sources; here we briefly discuss the roles of mitochondrial dysfunction and increased inflammation. Mitochondrial respiration, through the oxidation of glucose and/or fatty acids, can generate oxidative stress through the byproduct of generation of ATP in an oxygenated environment [ 55 , 56 ]. This process can be exacerbated in obesity due to the higher levels of available mitochondrial substrates, i.e., high glucose and fatty acids.…”
Section: Obesity and Oxidative Stressmentioning
confidence: 99%